EVALUASI RENCANA PEMBANGUNAN JANGKA MENENGAH DESA (STUDI KASUS DI DESA LUBUK SULI KECAMATAN DEPATI VII KABUPATEN KERINCI : AFRIYANTI, SE., M.Pd - AFRIANTI, SE., M.Pd (LPPM STIA Nusantara Sakti, 2020)
Development is a process of social change with broad participation a society that is intended to achieve social and material progress (including increasing the amount of justice, freedom and other valued qualities) for the majority of the people through the greater control they have over their environment. To plan development is not to build ideas and future strategies only without considering the social, cultural, and community adoption ability to change, so a lot of planning has been successful in stimulating economic growth in the short term but failed in building social cohesion, resisting vulnerability and reinforcing the cultural value. In relation to this, the village development planning should be put in a comprehensive manner to bridge the development needs of the region, strengthening the sector and harmonization of development actors.This study aims to see how the results of the evaluation of the Middle-Term Development Plan of the village of LubukSuli, DepatiTujuh District, Kerinci 2018 district. This type of research is a qualitative descriptive approach. Sources of data in this study using interviews and documentation. the general aspects of planning and implementation are good enough.